Prosthetic valve endocarditis after transcatheter aortic valve replacement in low‐risk patients. Issue 3 (10th September 2021) - Medranda, Giorgio A.; Rogers, Toby; Ali, Syed W.; Zhang, Cheng; Shea, Corey; Sciandra, Kathryn A.; Case, Brian C.; Forrestal, Brian J.; Sutton, Joseph A.; McFadden, Eugene P.; Malla, Prerna; Gordon, Paul; et al.
Abstract: Objectives: We sought to report details of the incidence, organisms, clinical course, and outcomes of prosthetic valve endocarditis (PVE) after transcatheter aortic valve replacement (TAVR) in low‐risk patients. Background: PVE remains a rare but devastating complication of aortic valve replacement. Data regarding PVE after TAVR in low‐risk patients are lacking. Methods: We performed a detailed review of all patients in the low‐risk TAVR trials who underwent TAVR from 2016 to 2020 and were adjudicated to have definitive PVE by the independent Clinical Events Committee. Results: We analyzed 396 low‐risk patients who underwent TAVR (including 72 with bicuspid valves). PVE occurred in 11 patients at a median 379 days (210, 528) from TAVR. The incidence within the first 30 days was 0%; days 31–365, 1.5%; and after day 365, 2.8%. The most common organism identified was Streptococcus ( n  = 4/11). Early PVE (≤ 365 days) occurred in five patients, of whom three demonstrated evidence of embolic stroke and two underwent surgical aortic valve re‐intervention. Late PVE (> 365 days) occurred in six patients, of whom thee demonstrated evidence of embolic stroke and only one underwent surgical aortic valve re‐intervention. Of the six patients with evidence of embolic stroke, two died, two were discharged to rehabilitation, and two were discharged home with home care. Conclusions: PVE was infrequent following TAVR in low‐risk patients but was associated with substantial morbidity and mortality. Embolic stroke complicated the majority of PVE cases, contributing to worse outcomes in these patients. Efforts must be undertaken to minimize PVE in TAVR.